Implementation Of Islamic Education Program Evaluation In Madrasah As An Effort To Improve The Quality Of Learning - Siti Umami; Rusdiana Navlia (Penerbit Hellow Pustaka, 2025)
Evaluation of Islamic education programs in madrasas plays a strategic role in ensuring that the quality of learning is aligned with national education goals and Islamic values. Planned, systematic, and continuous evaluation provides the basis for determining program effectiveness, teacher performance, and student achievement levels. This study aims to analyze the implementation of Islamic education program evaluation in madrasas as an effort to improve learning quality. Using a literature review approach, this study reviewed various scientific sources, books, and journals relevant to the topic of Islamic education evaluation. The results indicate that effective evaluation encompasses three main aspects: planning, implementation, and learning outcomes. Comprehensive evaluation enables madrasas to identify program weaknesses, improve the learning process, and continuously enhance educational quality. Therefore, program evaluation is not merely an administrative activity but also a strategic instrument in realizing superior, competitive, and Islamic-characterized madrasas.